Play and peril: Displacement drivers and types across recreation motivations in crowding and wildfire-prone southern California national forests - Alyssa S. Thomas; Erin E. Budzyn; Elizabeth E. Perry; Brian A. Peterson; José J. Sánchez (Journal of Outdoor Recreation and Tourism, 2025)

An investigation of force potential against the companion dog neck associated with collar use - Joshua Bailey; Dakota Discepolo; Janice Baker; Erin Perry (Journal of Veterinary Behavior, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Exposure to residential greenness, perceived stress, and depressive symptoms in a North American preconception cohort - Cameron J. Reimer; Mary D. Willis; Amelia K. Wesselink; Perry Hystad; Erin J. Campbell; Elizabeth E. Hatch; Kipruto Kirwa; Jaimie L. Gradus; Marco Vinceti; Lauren A. Wise; Marcia Pescador Jimenez (Environmental Research, 2024)

Impacts of olfactory cues on equine feeding behavior - Erin B. Perry; Grace C. Handlos; Jesse M. Fenton (Journal of Equine Veterinary Science, 2024)

Roadway construction as a natural experiment to examine air pollution impacts on infant health - Elaine Hill; Max Harleman; Lena Harris; Grace Sventek; Beate Ritz; Erin J. Campbell; Mary Willis; Perry Hystad (Environmental Research, 2024)

Assessment of the barrier function of canine skin after repeated decontamination - Dakota Discepolo; Russell Kelley; Erin Perry (Journal of Veterinary Behavior, 2023)

Coexistence between similar invaders: The case of two cosmopolitan exotic insects - Matthew B. Arnold; Michael Back; Michael Daniel Crowell; Nageen Farooq; Prashant Ghimire; Omon A. Obarein; Kyle E. Smart; Trixie Taucher; Erin VanderJeugdt; Kayla I. Perry; Douglas A. Landis; Christie A. Bahlai (Ecology, 2023)
Biological invasions are usually examined in the context of their impacts on native species. However, few studies have examined the dynamics between invaders when multiple exotic species successfully coexist in a novel environment. Yet, long‐term coexistence of now established exotic species has been observed in North American lady beetle communities. Exotic lady beetles Harmonia axyridis and Coccinella septempunctata were introduced for biological control in agricultural systems and have since become dominant species within these communities. In this study, we investigated coexistence via spatial and temporal niche partitioning among H. axyridis and C. septempunctata using a 31‐year data set from southwestern Michigan, USA. We found evidence of long‐term coexistence through a combination of small‐scale environmental, habitat, and seasonal mechanisms. Across years, H. axyridis and C. septempunctata experienced patterns of cyclical dominance likely related to yearly variation in temperature and precipitation. Within years, populations of C. septempunctata peaked early in the growing season at 550 degree days, while H. axyridis populations grew in the season until 1250 degree days and continued to have high activity after this point. C. septempunctata was generally most abundant in herbaceous crops, whereas H. axyridis did not display strong habitat preferences. These findings suggest that within this region H. axyridis has broader habitat and abiotic environmental preferences, whereas C. septempunctata thrives under more specific ecological conditions. These ecological differences have contributed to the continued coexistence of these two invaders. Understanding the mechanisms that allow for the coexistence of dominant exotic species contributes to native biodiversity conservation management of invaded ecosystems.

Ability of rbcL and matK DNA barcodes to discriminate between montane forest orchids - Samantha J. Worthy; Kylie Bucalo; Erin Perry; Alex Reynolds; Jennifer Cruse-Sanders; Álvaro J. Pérez; Kevin S. Burgess (Plant Systematics and Evolution, 2022)

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

New steps for treating alcohol use disorder - Erin J. Campbell; Andrew J. Lawrence; Christina J. Perry (Psychopharmacology, 2018)

Warming and provenance limit tree recruitment across and beyond the elevation range of subalpine forest - Lara M. Kueppers; Erin Conlisk; Cristina Castanha; Andrew B. Moyes; Matthew J. Germino; Perry de Valpine; Margaret S. Torn; Jeffry B. Mitton (Global Change Biology, 2017)
Climate niche models project that subalpine forest ranges will extend upslope with climate warming. These projections assume that the climate suitable for adult trees will be adequate for forest regeneration, ignoring climate requirements for seedling recruitment, a potential demographic bottleneck. Moreover, local genetic adaptation is expected to facilitate range expansion, with tree populations at the upper forest edge providing the seed best adapted to the alpine. Here, we test these expectations using a novel combination of common gardens, seeded with two widely distributed subalpine conifers, and climate manipulations replicated at three elevations. Infrared heaters raised temperatures in heated plots, but raised temperatures more in the forest than at or above treeline because strong winds at high elevation reduced heating efficiency. Watering increased season‐average soil moisture similarly across sites. Contrary to expectations, warming reduced Engelmann spruce recruitment at and above treeline, as well as in the forest. Warming reduced limber pine first‐year recruitment in the forest, but had no net effect on fourth‐year recruitment at any site. Watering during the snow‐free season alleviated some negative effects of warming, indicating that warming exacerbated water limitations. Contrary to expectations of local adaptation, low‐elevation seeds of both species initially recruited more strongly than high‐elevation seeds across the elevation gradient, although the low‐provenance advantage diminished by the fourth year for Engelmann spruce, likely due to small sample sizes. High‐ and low‐elevation provenances responded similarly to warming across sites for Engelmann spruce, but differently for limber pine. In the context of increasing tree mortality, lower recruitment at all elevations with warming, combined with lower quality, high‐provenance seed being most available for colonizing the alpine, portends range contraction for Engelmann spruce. The lower sensitivity of limber pine to warming indicates a potential for this species to become more important in subalpine forest communities in the coming centuries.

Population ecology of the snail Melampus bidentatus in changing salt marsh landscapes - Roman Zajac; Erin Kelly; Danielle Perry; Ivana Espinosa (Marine Ecology, 2017)
We studied the population ecology of the snail Melampus bidentatus in relation to patch composition and landscape structure across several salt marsh systems in Connecticut, USA . These marshes have changed significantly over the past 40–50 years including loss of total area, increased areas of short Spartina alterniflora , and decreased areas and fragmentation of Spartina patens . These changes are consistent with tidal inundation patterns that indicate frequent flooding of high marsh areas. Melampus bidentatus densities were highly variable, both among different salt marsh systems and locations within specific marshes, but were generally similar among short Sp. alterniflora and Sp. patens patches within locations. Densities were lowest where the marsh was regularly inundated at high tide and only remnant Sp. patens patches remained. Almost no snails were found in bare patches. Areas that had large Sp. patens patches adjacent to short Sp. alterniflora supported the highest M. bidentatus densities. Population size‐structure varied significantly among patch types, with higher proportions of large individuals in short Sp. alterniflora and hummocked Sp. patens patches than in large and remnant Sp. patens patches. This was likely due to size‐selective predation and/or higher snail growth rates due to better food resource conditions in short Sp. alterniflora patches. Egg mass densities and the number of eggs per egg mass were highest in short Sp. alterniflora . Our results indicate that M. bidentatus is resilient to the level and patterns of salt marsh change evident at our study sites. Indeed, snail densities were significantly higher than reported in other field studies, suggesting that increased patch areas of short Sp. alterniflora and associated environmental conditions at our study sites may provide more favorable habitats than previously when marshes were dominated by extensive Sp. patens meadows. However, there may be threshold conditions that could overwhelm the ability of M. bidentatus to maintain itself within salt marsh systems where changes in hydrology, sedimentation and other factors lead to increased numbers of bare patches and ponds and loss of short Sp. alterniflora and Sp. patens . Studies of the responses of resident and transient fauna to salt marsh change are critically needed in order to better understand the implications for salt marsh ecosystem dynamics and services.

Climate and edaphic controllers influence rhizosphere community assembly for a wild annual grass - Erin E. Nuccio; James Anderson‐Furgeson; Katerina Y. Estera; Jennifer Pett‐Ridge; Perry de Valpine; Eoin L. Brodie; Mary K. Firestone (Ecology, 2016)
The interface between roots and soil, known as the rhizosphere, is a dynamic habitat in the soil ecosystem. Unraveling the factors that control rhizosphere community assembly is a key starting point for understanding the diversity of plant‐microbial interactions that occur in soil. The goals of this study were to determine how environmental factors shape rhizosphere microbial communities, such as local soil characteristics and the regional climate, and to determine the relative influence of the rhizosphere on microbial community assembly compared to the pressures imposed by the local and regional environment. We identified the bacteria present in the soil immediately adjacent to the roots of wild oat ( Avena spp .) in three California grasslands using deep Illumina 16S sequencing. Rhizosphere communities were more similar to each other than to the surrounding soil communities from which they were derived, despite the fact that the grasslands studied were separated by hundreds of kilometers. The rhizosphere was the dominant factor structuring bacterial community composition (38% variance explained), and was comparable in magnitude to the combined local and regional effects (22% and 21%, respectively). Rhizosphere communities were most influenced by factors related to the regional climate (soil moisture and temperature), while background soil communities were more influenced by soil characteristics ( pH , CEC , exchangeable cations, clay content). The Avena core microbiome was strongly phylogenetically clustered according to the metrics NRI and NTI , which indicates that selective processes likely shaped these communities. Furthermore, 17% of these taxa were not detectable in the background soil, even with a robust sequencing depth of approximately 70,000 sequences per sample. These results support the hypothesis that roots select less abundant or possibly rare populations in the soil microbial community, which appear to be lineages of bacteria that have made a physiological tradeoff for rhizosphere competence at the expense of their competitiveness in non‐rhizosphere soil.

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

Impulsivity (delay discounting) as a predictor of acquisition of IV cocaine self-administration in female rats - Jennifer L. Perry; Erin B. Larson; Jonathan P. German; Gregory J. Madden; Marilyn E. Carroll (Psychopharmacology, 2005)

Interspecific Interactions Between Cebus capucinus and Other Species: Data from Three Costa Rican Sites - Lisa M. Rose; Susan Perry; Melissa A. Panger; Katharine Jack; Joseph H. Manson; Julie Gros-Louis; Katherine C. Mackinnon; Erin Vogel (International Journal of Primatology, 2003)